Bad education [videorecording (DVD)] - Almodóvar, Pedro; García Bernal, Gael, 1978-; Martínez, Fele; Giménez Cacho, Daniel (Sony Pictures Classics, 2005)
Traces the effects of sexual abuse and religious schooling on the lives of two lifelong friends.